Resection for Klatskin tumors: technical complexities and results - Capobianco, Ivan; Rolinger, Jens; Nadalin, Silvio (Translational Gastroenterology and Hepatology, 2018)
Klatskin’s tumors, actually-redefined as perihilar cholangiocarcinoma (phCCA) do represent 50–70% of all CCAs and develop in a context of chronic inflammation and cholestasis of bile ducts. Surgical resection provides the only chance of cure for this disease but is technically challenging because of the complex, intimate and variable relationship between biliary and vascular structures at this location. Five years survival rates range between 25–45% (median 27–58 months) in case of R0 resection and 0–23% (median 12–21 months) in case of R1 resection respectively. It should be noted that the major costs of high radicality are represented by relative high morbidity and mortality rates (i.e., 20–66% and 0–9% respectively). Considering the fact that radical resection may represent the only curative treatment of phCCA, we focused our review on surgical planning and techniques that may improve resectability rates and outcomes for locally advanced phCCA. The surgical treatment of phCCA can be successful when following aspects have been fulfilled: (I) accurate preoperative diagnostic aimed to identify the tumor in all its details (localization and extension) and to study all the risk factors influencing a posthepatectomy liver failure (PHLF): i.e., liver volume, liver function, liver quality, haemodynamics and patient characteristics; (II) High end surgical skills taking in consideration the local extension of the tumor and the vascular invasion which usually require an extended hepatic resection and often a vascular resection; (III) adequate postoperative management aimed to avoid major complications (i.e., PHLF and biliary complications). These are technically challenging operations and must be performed in a high volume centres by hepato-biliary-pancreas (HBP)-surgeons with experience in microsurgical vascular techniques.